Review on Additive Manufacturing of Catalysts and Sorbents and the Potential for Process Intensification - Rosseau, Leon R.S.; Middelkoop, Vesna; Willemsen, Hans A.M.; Roghair, Ivo; van Sint Annaland, Martin (Frontiers in Chemical Engineering, 2022)
Additive manufacturing of catalyst and sorbent materials promises to unlock large design freedom in the structuring of these materials, and could be used to locally tune porosity, shape and resulting parameters throughout the reactor along both the axial and transverse coordinates. This contrasts catalyst structuring by conventional methods, which yields either very dense randomly packed beds or very open cellular structures. Different 3D-printing processes for catalytic and sorbent materials exist, and the selection of an appropriate process, taking into account compatible materials, porosity and resolution, may indeed enable unbounded options for geometries. \\In this review, recent efforts in the field of 3D-printing of catalyst and sorbent materials are discussed. It will be argued that these efforts, whilst promising, do not yet exploit the full potential of the technology, since most studies considered small structures that are very similar to structures that can be produced through conventional methods. In addition, these studies are mostly motivated by chemical and material considerations within the printing process, without explicitly striving for process intensification. To enable value-added application of 3D-printing in the chemical process industries, three crucial requirements for increased process intensification potential will be set out: i) the production of mechanically stable structures without binders; ii) the introduction of local variations throughout the structure; and iii) the use of multiple materials within one printed structure.